A TDLAS Sensor for Simultaneous Measurement of Temperature and C2H4 Concentration Using a Differential Absorption Scheme at High Temperature - Zhang, Ting; Zhang, Gang; Liu, Xin; Gao, Guangzhen; Cai, Tingdong (Frontiers in Physics, 2020)
The ethylene (C2H4) concentration and temperature are simultaneously measured in high temperature environment using a differential absorption scheme combined with a distributed feedback (DFB) diode laser near 1.620 μm. Based on optimal selection criterions, two wavelength pairs with absorption peaks at 6174.58 cm-1 and 6174.98 cm-1 are selected for the measurement. Temperature are obtained from the ratio of the absorption cross section of the two wavelength pairs, and C2H4 concentration is inferred from the differential absorption of one of the wavelength pairs. Measurements are performed in a high temperature cell (T = 300-900 K, P = 1 atm) to verify the accuracy of the system. The accuracies for the measurement of C2H4 concentration and temperature are 1.135% and 2.215%, respectively. Continuous time series measurements indicated that the system has a good stability and the limit of detection achieved by Allan-Werle variance analysis is 6.6 ppm at the optimal average time of 340 s. All the measurements show the scheme is helpful to improve the practicality of laser absorption spectroscopy in combustion diagnosis.